Dissolution of the Union of Soviet Socialist Republics and formation of independent state of Kazakhstan - Kozhakhmetov, G.Z.; Botagarin, R.B. (KSU publ., 2016)
The article gives a detailed analysis of economic and political reasons for the dissolution of the Union of Soviet Socialist Republics and the features of independent Kazakhstan formation. In order to disclose the contents the authors of the article draw the conclusions based on historic facts. They analyze the obstacles and historical processes connected with the appearance of independent Kazakhstan on historical arena.
Keywords: dissolution; the Union of Soviet Socialist Republics; the Republic of Kazakhstan; Russia; independence